FORMULASI KEBIJAKAN PELARANGAN AKTIVITAS PENAMBANGAN EMAS TANPA IZIN DI SEPANJANG ALIRAN SUNGAI DALAM WILAYAH DESA LUBUK TERENTANG - Adini Nurul Vatani; Sujianto " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2020)
Gold is one type of mining material that has very high economic value. Due to the economic value the villagers use as a livelihood, this activity involves dompeng or unauthorized gold mining (PETI) along the Kuantan Singi River. Lubuk Terentang Village is one of the villages located in Kuantan Singingi which is not entered by illegal gold mining activities (PETI) which have an impact on the surrounding environment. This occurs because ofthe  policy bottom-up  agreed by the village government and community to prohibit illegal activity shaped joint decree. This study aims to determine: (1). The formulation process for the prohibition of unlicensed gold mining activities in Lubuk Terentang village, (2). The success factor of the formulation of the prohibition of unlicensed gold mining activities in Lubuk Terentang village. This study uses a qualitative method with a descriptive case study approach. Informants were taken using purposive sampling method. Data collection was carried out by observation, interviews, and documentation. The data analysis used a qualitative descriptive method. The results showed that the formulation process of the joint decree was deliberation carried out by the village government and the community represented by Ninik / Mamak and village youth. The supporting factors are the role of people who are aware of the environment and the role of public actors who only become facilitators in the formulation process without any interest in it. Keywords : Public Policy, Policy Formulation,Policy Bottom-up